New Vectors of the Development of Cultural and Sports Diplomacy Caused by the 2022 Russian-Ukrainian War - Shuliak, Antonina M.; Melnychuk, Liubov; Kulyk, Serhii M.; Mykhaliuk, Nazar Yu.; Panas, Viktoriia; Palokha, Nataliia (My University, 2022)
Russia's armed aggression against Ukraine actualized the research of Ukrainian and foreign scientists on the use of opportunities of cultural and sports diplomacy during armed conflicts. The article analyzes how representatives of the world artistic and sports community reacted to the war in Ukraine and what forms and methods were used by Ukrainian artists and athletes to articulate and protect the national interests of Ukraine on its territory and abroad. It has been proven that in this way they drew the attention of the public, state authorities of the countries of the world to the conflict in Ukraine, Russia's violation of international law and contempt for moral values and human life. Artists and athletes initiated, tested, and successfully proved the effectiveness of new tools and means of cultural and sports diplomacy. The universality of this diplomacy in international relations, the ease of its perception and dissemination in society, combined with the creative approach of its participants in response to changes in world politics determined the development of its new vectors. The effectiveness of these forms and methods lies in the fact that they: 1) helped to relatively quickly inform the public of the countries of the world about Russia's aggression in Ukraine; 2) recognized artists and “stars” of sports willingly joined it; 3) initiated by them, their foreign colleagues, citizens of other countries, football matches, public actions, performances gained public resonance and support in Ukraine and abroad; 4) reached a large audience of various ages; 5) ensured the receipt of funds for the needs of Ukraine to charitable funds; 6) contributed to the establishment of a positive image of Ukraine and Ukrainians, countries of the world that joined these actions. All these efforts were generally aimed at countering “Russian World” and Putin's “rashism”.
Keywords: Culture; Sport; Diplomacy; Russia; Ukraine; War; Artists; Athletes; Performances